Distinct patterns of naive, activated and memory T and B cells in blood of patients with ulcerative colitis or Crohn's disease. (8th April 2019) - Rabe, H; Malmquist, M; Barkman, C; Östman, S; Gjertsson, I; Saalman, R; Wold, A E
Summary: Both major subcategories of inflammatory bowel disease (IBD), ulcerative colitis and Crohn's disease are characterized by infiltration of the gut wall by inflammatory effector cells and elevated biomarkers of inflammation in blood and feces. We investigated the phenotypes of circulating lymphocytes in the two types of IBD in treatment-naive pediatric patients by analysis of blood samples by flow cytometry. Multivariate analysis was used to compare the phenotypes of the blood lymphocytes of children with ulcerative colitis ( n = 17) or Crohn's disease ( n = 8) and non-IBD control children with gastrointestinal symptoms, but no signs of gut inflammation ( n = 23). The two IBD subcategories could be distinguished based on the results from the flow cytometry panel. Ulcerative colitis was characterized by activated T cells, primarily in the CD8 + population, as judged by increased expression of human leukocyte antigen D-related (HLA-DR) and the β1-integrins [very late antigen (VLA)] and a reduced proportion of naive (CD62L + ) T cells, compared with the non-IBD controls. This T cell activation correlated positively with fecal and blood biomarkers of inflammation. In contrast, the patients with Crohn's disease were characterized by a reduced proportion of B cells of the memory CD27 + phenotype compared to the non-IBD controls. Both the patients with ulcerative colitis and those with Crohn's disease showed increased percentages of CD23 + B cells, which we demonstrate here as being naive B cells. The results support the notion that the two major forms of IBD may partially have different pathogenic mechanisms. Graphical Abstract: